Column adsorption and regeneration study of magnetic biopolymer resin for perchlorate removal in presence of nitrate and phosphate. (10th March 2019) - Pan, Jingwen; Gao, Baoyu; Song, Wen; Xu, Xing; Jin, Bo; Yue, Qinyan
Abstract: A magnetized and quaternary amine-functionalized bio-resin derived from corn stalk (CS-MNB) was successfully synthesized and applied for perchlorate removal by combining of column adsorption and biological/chemical regeneration in presence of nitrate and phosphate. Characterization by SEM, TEM, XRD, Zeta potential, BET and XPS revealed that CS-MNB had well-developed pore structure, large surface area and lots of quaternary-amine groups, enhancing the diffusion and removal of anion. Column adsorption of co-anions was investigated considering the bed depths, flow rates, influent pHs and anion concentrations using CS-MNB. The performance of fixed-bed column was optimal at the condition of bed depth of 2.15 cm, flow rate of 5 mL/min, and pH 4. The maximum adsorption capacities of CS-MNB were calculated to be 23.16, 6.48 and 48.73 mg/g for perchlorate, nitrate and phosphate, respectively. These three anions could be efficiently removed by the magnetic bio-resin, through an ion-exchange reaction between Cl − in quaternary amine groups and the dissolved anions. After being adsorbed by the bio-resin, the concentrated anions could be efficiently bio-reduced by the acclimated sludge predominated by Proteobacteria species. The simultaneous perchlorate and nitrate reductions were achieved by biological regeneration, although a lower bio-regeneration efficiency (26–89%) was observed as compared with that of chemical regeneration (90–93%). Graphical abstract: Image 1 Highlights: Efficient column adsorption of perchlorate in presence of nitrate and phosphate. Perchlorate has the strongest binding force with the adsorption site. Effective reuse of bio-resin can be achieved by chemical and biological regeneration. A relatively stable bio-resin within long-term adsorption.